Improvisação dança cognição: os processos de comunicação no corpo - Martins, Cleide (2002)
This work is structured on the hypothesis that improvisation is a communication processo For the construction of this hypothesis, its understood that a body that dances receives information fIam lhe world, information that comes to be intemalized by the body that dances. This body continues to change the intemalized information -now modified - with the world. All the time the changes between the inner and the outer are permanent. This is what is called systemic co-evolution. For this reason, the communication between environrnent and body is extended in time. The understanding of this process results in another way of presenting the relation of subjects with the things of the world, aTIce subject and world loose their separated positions, and are viewed as implicating one another. Subjects stop being distant observers. The improvisation is capable of creating, permitting, supporting a complex system, which is said to be auto-organized when itself acquires autonomy, creates innovation in a coherent way. New arrangements and the combinatory process of actions and movements produced in lhe improvisation permit us to know and leam with our bodies. To consolidate this proposal of communication, dynamicist explanations of Esther Thelen, Timothy van Gelder, and Robert Port are fundamental, as well as Mario Bunge's systemic perspective is the appropriate framework